INFLUENCE OF SALINITY ON ECOPHYSIOLOGICAL CHARACTERISTICS OF WINTER WHEAT VARIETIES (Web of Teachers: Inderscience Research, 2025)
The article describes the adaptation of wheat varieties to soil salinity. Stress factors affecting the physiological processes of wheat. Identification of mechanisms of plant resistance to salt stress is one of the most pressing theoretical and scientific problems in the world, вy deepening scientific research work in this area, much attention is paid to the creation of methods for using exogenous and endogenous substances to increase the resistance of wheat to stress factors, the widespread use of the existing gene pool of agricultural crops in genetic selection research and widespread implementation in agricultural production.